Manajemen Tenaga Pendidik dan Strategi Pembelajaran - Zulkarnainsyah Zulkarnainsyah (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2020)
Management as an ability or expertise which later became the forerunner of management as a profession. Management as a science that emphasizes attention to managerial skills and abilities which are classified into technical, human and conceptual abilities / skills. Management as a process by determining systematic and integrated steps as a management activity. Management as an art is reflected in differences in one's style in using or empowering others to achieve goals. Educational management is a management process in the implementation of educational tasks by using all sources efficiently to achieve goals effectively. Educators in the educational process play a strategic role, especially in an effort to shape the character of the nation through personal development and desired values. As educators, teachers are one of the determining factors for the success of every effort in achieving educational goals. Therefore, the increase in human resources that is expected from efforts to achieve education which is a very important factor is the role of a teacher. Tasks include educating teachers as a profession, teaching and training. The strategy is intended as a teacher's effort to create an environmental system that allows the learning process to occur. The learning process is at the core of the overall educational process with the teacher as the main role holder.